Life after surgical resection of a low-grade glioma: A prospective cross-sectional study evaluating health-related quality of life. (June 2021) - Teng, Ken X.; Price, Benjamin; Joshi, Shubhum; Alukaidey, Lobna; Shehab, Ameer; Mansour, Kristy; Toor, Gurvinder S.; Angliss, Rosemary; Drummond, Katharine
Highlights: Low grade glioma patients report limitations in HRQoL for>120 months after surgery. Cognitive, emotional, and social functioning are most impacted. Patients also experience significant fatigue and insomnia. These functional impairments and symptoms are strongly associated with global HRQoL. Interventions targeting these domains and symptoms may improve HRQoL for LGG patients. Abstract: Health related quality of life (HRQoL) has become an important consideration in LGG patients. We report the largest prospective, longitudinal, cross-sectional cohort study of HRQoL in LGG patients, aiming to identify actionable determinants of HRQoL. Post-operative LGG adults at a large tertiary center underwent HRQoL assessment using the EORTC QLQ-C30 questionnaire administered at follow-up visits and by mail. Scores at 12 month intervals were compared with those from a normative reference population. Spearman's Rho was used to evaluate correlation of subdomain and symptom scores with global HRQoL and change over time. There were 167 participants and 366 questionnaires analysed. Patients reported reduced global HRQoL at nearly every 12 month interval with significant impairments at 12, 72, 108, and 120+ months postoperative. They also reported a significant impairment in each functional subdomain at 12 months, which persisted to varying degrees over 120 months, as did significant fatigue and insomnia. Role, emotional, and social subdomains, as well as fatigue, were significantly associated with global HRQoL at the first 12 month interval. Overall, there was no significant correlation between time from surgery and global HRQoL or the subdomain functional or symptom sections of the QLQ-C30. LGG patients report considerable, sustained impairments in HRQoL after surgery, particularly in cognitive, emotional, and social function, as well as suffering significant fatigue and insomnia. These are strongly associated with global HRQoL and thus can be considered determinants of global HRQoL that with intervention, may improve HRQoL for our LGG patients. This is the largest prospective longitudinal study of HRQoL in postoperative LGG patients yet reported and is ongoing. It identifies several determinants of impaired HRQoL with available management options and interventions that have the potential to significantly improve HRQoL in these patients.